Tibial shock measured during the fencing lunge: the influence of footwear - Sinclair, J.; Bottoms, L.; Taylor, K.; Greenhalgh, A. (Sports Biomechanics, 2010)
Fencing is a high-intensity sport involving dynamic movements such as the lunge exposing the musculoskeletal system to high impact forces, which emphasises the importance of the shock attenuating properties of footwear as a factor in the prevention of injury. The aim of this study was to investigate the magnitudes of the transient axial impact shock experienced at the tibia between traditional fencing shoes and standard athletic footwear during the impact phase of the fencing lunge. Peak tibial shock was measured in 19 male fencers in 4 different footwear conditions using an accelerometer placed on the distal aspect of the tibia. The standard footwear (11.08 g and 8.75 g for squash and running shoe, respectively) resulted in significant ( p , 0.01) reductions in peak impact shock in comparison to the traditional fencing shoes (15.93 g and 13.97 g for the Adidas and Hi-Tec shoe, respectively). No significant differences were found between the running and squash shoes ( p ¼ 0.09) or between the fencing shoes ( p ¼ 0.48). The documented reduction in impact shock found suggests that running or squash specific footwear may reduce overuse injury occurrence, indicating that there is justification for a re-design of fencing shoes.